CONTINUITY AND CHANGE IN THE PURPOSE OF A LONG LIFE: INTERNATIONAL PERSPECTIVES. (11th November 2018) - Biggs, S; Siren, A
Abstract: The tension between continuity and discontinuity is a key element in examining the development of meaning in later life. This in part because of the closer association between biological, psychological and social change as one grows older and in part because of an increasing imperative to somehow manage our identities in the context of structural, interpersonal and personal disruption. When examining the effects of population ageing these questions become critically engaged, not only between the supposed purpose of a long life, but also of how to negotiate ageing in the context of generational groups that are approaching approximately the same size. This symposium will examine how these tensions are played out in a number of critical contexts, including: a critical approach to intergenerational learning and lifecourse modelling, fears associated with old age including dementia, frailty and suffering, great grandparenting as a role mediating meaning making, cultural disruptions associated with generations in Greenland communities, plus means of interrogating social policy from an intergenerational perspective. Implications will be discussed in terms of the continuity and change in position of older people in society and the purpose of a long life in an intergenerational context.